A mitotic CDK5-PP4 phospho-signaling cascade primes 53BP1 for DNA repair in G1 - Xiao-Feng Zheng (Nature Portfolio, 2019)
Regulation of post translational modification of 53BP1 is critical for genome integrity and regulation of DNA damage response. Here the authors reveal a CDK5-PP4 phospho-signaling cascade that leads 53BP1 to sites of DNA damage.